Optimal control problem for Lengyel–Epstein model with obstacles and state constraints - Zheng, Jiashan (Nonlinear Analysis: Modelling and Control, 2016)
This paper considers the state constrained optimal control problem for Lengyel–Epstein model with obstacles. We prove existence and regularity results for this model by applying the standard methods. We show the relationship between the control problem and its approximation. Moreover, we derive the necessary conditions for the optimal control of our original problem by using the approximate problem.
Keywords: Lengyel–Epstein model; optimal control; necessary conditions; obstacles